ChemInform Abstract: Tuning the Activity of Pt Alloy Electrocatalysts by Means of the Lanthanide Contraction. Issue 27 (16th June 2016) - Escudero‐Escribano, Maria; Malacrida, Paolo; Hansen, Martin H.; Vej‐Hansen, Ulrik G.; Velazquez‐Palenzuela, Amado; Tripkovic, Vladimir; Schiotz, Jakob; Rossmeisl, Jan; Stephens, Ifan E. L.; Chorkendorff, Ib
Abstract: The oxygen reduction reaction (ORR) is investigated on sputter‐cleaned polycrystalline Pt5 M (M: La, Ce Sm, Gd, Tb, Dy, Tm, Ca) catalyst cathodes of polymer electrolyte membrane fuel cells.